UPPER OLIGOCENE BRACHIOPODS FROM NW GERMANY, WITH DESCRIPTION OF A NEW PLATIDIINAE GENUS, GERMANOPLATIDIA N. GEN. (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Upper Oligocene brachiopods of NW Germany were studied in two collections: the Naturalis Biodiversity Center (Leiden, the Netherlands) and the F. von der Hocht private Collection (Kerpen, Germany). Overall, six brachiopod taxa have been identified. Generic attributions of “Rhynchonella” supraoligocaenica Görges, 1952 (Aphelesia) and “Terebratula” pusilla Philippi, 1843 (Germanoplatidia n. gen) have been solved. The Chattian occurrence of Aphelesia is the first confirmed record of the genus in the Paleogene. Chattian record of the well-known Neogene Discinisca fallens (Wood, 1872) confirms that faunal change within brachiopods happened before the Paleogene/Neogene boundary. Similarly to the Mediterranean Terebratula-Aphelesia association, Aphelesia occurs also together with a large terebratulide genus (Pliothyrina) in the upper Oligocene Pre-North Sea. Along with some previously recognized genera (Orthothyris, Bronnothyris, Rugia), a further brachiopod evolutionary lineage was found to survive from the Mesozoic to the Paleogene (Aemula-Germanoplatidia n. gen.). According to the morphological characters of the genus and sedimentological characters of the surrounding deposits, Germanoplatidia n. gen. species lived on sandy bottom environments, and attached to small hard objects in the fine sediment by a pedicle longer than that of Aemula. Half of the identified species are endemic in Pre-North Sea. Here we document the first record of Argyrotheca bitnerae Dulai in Dulai & Stachacz, 2011 from the Pre-North Sea; this recently described species shows a cosmopolitan distribution in the Cenozoic.
Keywords: Brachiopoda; Chattian; Germanoplatidia; new genus; Platidiidae; Pre-North Sea Basin.